Influence of rotator cuff tears on glenohumeral stability during abduction tasks. Issue 9 (21st January 2016) - Hölscher, Thomas; Weber, Tim; Lazarev, Igor; Englert, Carsten; Dendorfer, Sebastian
ABSTRACT: One of the main goals in reconstructing rotator cuff tears is the restoration of glenohumeral joint stability, which is subsequently of utmost importance in order to prevent degenerative damage such as superior labral anterior posterior (SLAP) lesion, arthrosis, and malfunction. The goal of the current study was to facilitate musculoskeletal models in order to estimate glenohumeral instability introduced by muscle weakness due to cuff lesions. Inverse dynamics simulations were used to compute joint reaction forces for several static abduction tasks with different muscle weakness. Results were compared with the existing literature in order to ensure the model validity. Further arm positions taken from activities of daily living, requiring the rotator cuff muscles were modeled and their contribution to joint kinetics computed. Weakness of the superior rotator cuff muscles (supraspinatus; infraspinatus) leads to a deviation of the joint reaction force to the cranial dorsal rim of the glenoid. Massive rotator cuff defects showed higher potential for glenohumeral instability in contrast to single muscle ruptures. The teres minor muscle seems to substitute lost joint torque during several simulated muscle tears to maintain joint stability. Joint instability increases with cuff tear size. Weakness of the upper part of the rotator cuff leads to a joint reaction force closer to the upper glenoid rim. This indicates the comorbidity of cuff tears with SLAP lesions. The teres minor is crucial for maintaining joint stability in case of massive cuff defects and should be uprated in clinical decision‐making. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1628–1635, 2016.